Relationship of prognostic nutritional index with anemia and all-cause mortality: a NHANES study - Yongjin Zhi; Shuojing Bao; Jingcheng Mao; Hui Zhu; Jianfeng Zhu (Hematology)
Background The present study systematically explores the correlation between the Prognostic Nutritional Index (PNI) and anemia, and further analysis of its association with all-cause mortality among populations affected by anemia.Methods Data were taken from the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2018. We utilized multiple logistic regression models, Cox proportional hazards models, restricted cubic spline (RCS) analysis, and time-dependent receiver operating characteristic (ROC) analysis. As for the verification of the result robustness, subgroup and sensitivity analyses were implemented.Results A cohort of 28,511 participants was examined, of whom 2647 (9.28%) had anemia. An inverse relationship of PNI with anemia was detected in the fully adjusted model (OR = 0.82, 95%CI: 0.80–0.84). Cox regression showed that lower PNI levels were linked to higher all-cause mortality in people with anemia (HR = 0.91, 95%CI: 0.88–0.95). A non-linear correlation between PNI and mortality was detected through RCS analysis (P < 0.001). Significant interaction effects of PNI with mortality were observed across diabetes and BMI subgroups (P < 0.05). The predictive power of PNI for all-cause mortality among anemia individuals showed areas under the curve (AUC) values of 0.702, 0.806, and 0.813 for 3-, 5-, and 10-year predictions, respectively.Conclusion PNI demonstrates a negative association with anemia and a similar negative relationship with all-cause mortality in individuals with anemia. Future studies are warranted to substantiate these findings.